Manganese vacancy-confined single-atom Ag in cryptomelane nanorods for efficient Wacker oxidation of styrene derivatives. Issue 17 (29th March 2021) - Yang, Hongling; Zhang, Xun; Yu, Yi; Chen, Zheng; Liu, Qinggang; Li, Yang; Cheong, Weng-Chon; Qi, Dongdong; Zhuang, Zewen; Peng, Qing; Chen, Xin; Xiao, Hai; et al.
Abstract : Manganese vacancy-confined single-atom Ag in cryptomelane nanorods efficiently catalyses Wacker oxidation of styrene derivatives. Abstract : Single-atom catalysts provide a pathway to elucidate the nature of catalytically active sites. However, keeping them stabilized during operation proves to be challenging. Herein, we employ cryptomelane-type octahedral molecular sieve nanorods featuring abundant manganese vacancy defects as a support, to periodically anchor single-atom Ag. The doped Ag atoms with tetrahedral coordination are found to locate at cation substitution sites rather than being supported on the catalyst surface, thus effectively tuning the electronic structure of adjacent manganese atoms. The resulting unique Ag–O–MnO x unit functions as the active site. Its turnover frequency reaches 1038 h −1, one order of magnitude higher than for previously reported catalysts, with 90% selectivity for anti-Markovnikov phenylacetaldehyde. Mechanistic studies reveal that the activation of styrene on the ensemble site of Ag–O–MnO x is significantly promoted, which can accelerate the oxidation of styrene and, in particular, the rate-determining step of forming the epoxide intermediate. Such an extraordinary electronic promotion can be extended to other single-atom catalysts and paves the way for their practical applications.